Assessing Biogas from Wastewater Treatment Plants for Sustainable Transportation Fuel: A Detailed Analysis of Energy Potential and Emission Reductions - Cagri Un (Gases)
This study assesses the potential for biogas production from wastewater treatment plants (WWTPs) in Adana, Türkiye, and evaluates the feasibility of transitioning a fleet of 83 municipal buses (ranging from 15 to 24 years old) to operate exclusively on biogas generated from these WWTPs. Biogas production data from three distinct WWTPs in Adana were analyzed, revealing a total annual biogas production of 5,394,346 Nm3. Replacing the diesel fleet with biogas-powered buses was found to yield a significant reduction in environmental impacts. CO2 emissions were reduced by 84%, particulate matter emissions decreased by 84.4%, and nitrogen oxides (NOX) dropped by 80%. These findings highlight the substantial potential of wastewater-derived biogas as a renewable energy source in public transportation, not only reducing reliance on non-renewable fuels but also contributing to improved air quality and energy efficiency. Transitioning to biogas-powered buses presents a promising model for sustainable public transportation, with broader implications for reducing the environmental footprint of urban transit systems.